Predictive screening of ionic liquids for dissolving cellulose and experimental verification. Issue 23 (12th September 2016) - Liu, Yan-Rong; Thomsen, Kaj; Nie, Yi; Zhang, Suo-Jiang; Meyer, Anne S.
Abstract : The cellulose dissolution ability of 357 ionic liquids (ILs) formed from 17 cations and 21 anions was assessed by COSMO-RS prediction; three models for cellulose were compared; 7 of the ILs were evaluated experimentally for ability to dissolve cellulose. Abstract : In this work, 357 ionic liquids (ILs) formed from 17 cations and 21 anions were selected for evaluation of their ability to dissolve cellulose by COSMO-RS. In order to evaluate the predictive model and method, experimental measurements of the solubility of microcrystalline cellulose (MCC) in 7 of these ILs were also conducted. Predicted results from logarithmic activity coefficients were generally in good agreement with the experimental results. Three different models were used for describing cellulose, and the mid-monomer part of the cellotriose model was found to be closer to the experimental results than a neat glucose model and the model of the mid-dimer part of cellotetraose. Excess enthalpy calculations indicated that hydrogen-bond (H-bond) interactions between cellulose ( i.e. the three cellulose models) and the 7 studied ILs are key factors for the solubility of cellulose, and the anions play a crucial role in the cellulose dissolution process. Importantly, the cations of methylimidazolium +, pyridinium +, ethylmorpholinium + and methylpyrrolidinium + structured with functional groups including ethyl, allyl, 2-hydroxylethyl, 2-methoxyethyl and acryloyloxypropyl, combined with anions Ac −, Dec −, HCOO −, Cl −, BEN −, DMPO4 −, DEP −, DBP − and Br − were predicted to be the best for dissolving cellulose.